Myelomeningocele: a Brazilian University Hospital experience Mielomeningocele: experiência de um hospital universitário brasileiro - Maria M.M. Ulsenheimer; Sérgio A. Antoniuk; Lúcia H.C. dos Santos; Marcos P. Ceccatto; Antônio Ernesto da Silveira; Ana Paula Ruiz; Paulo Egger; Isac Bruck (Arquivos de Neuro-Psiquiatria)
We analyzed 31 children with myelomeningocele born between July 1990 and July 2000. Follow-up median was 24 months (6-68months). Only 2 mothers had a known etiologic factor (diabetes mellitus). Twelve had the correct prenatal diagnosis. All children were born at term; 23 by cesarean; 13 had rupture of the membrane. Surgical correction had a 4 days median (1 to 44 days). Lumbosacral lesions were the most frequent (46%). Thirty patients were hydrocephalic, shunt was placed in 27. Meningitis was 4 times more frequent in shunted patients. Seven became epileptic (19.4%). Denver II test showed significant delay in gross motor development . Neurogenic bladder was diagnosed in 12 patients. Congenital clubfoot was the main orthopedic malformation (53%). Six infants died. Nowadays, 17 patients are being followed. A multidisciplinary approach probably helps for a better quality of life. Avaliamos 31 crianças com mielomeningocele nascidas entre julho de 1990 e julho de 2000. A mediana de acompanhamento foi 24 meses (6-68m). Duas mães possuíam conhecido fator de risco (diabetes mellitus). Doze obtiveram correto diagnóstico pré-natal da patologia. Todas as crianças nasceram a termo; 23 via cesariana; 13 apresentaram ruptura de membrana. A mediana de correção cirúrgica foi 4 dias (1-44d). Lesões lombosacras foram as mais freqüentes (46%). Trinta pacientes apresentaram hidrocefalia, sendo a derivação ventrículo peritoneal (DVP) necessária em 27. Meningite foi 4 vezes mais frequente em pacientes com DVP. Sete pacientes eram epilépticos (19,4%). O teste de Denver II mostrou atraso motor significante. Bexiga neurogênica foi diagnosticada em 12 pacientes. Pé torto congênito foi a malformação ortopédica mais comum (53%). Seis pacientes morreram. Até o momento, 17 pacientes são acompanhados. Uma abordagem multidisciplinar provavelmente colabora para melhor qualidade de vida.